A case of splenic artery pseudoaneurysm rupture presenting as rectal bleeding in a regional hospital. Issue 12 (17th December 2020) - Holt, Jonathon N; Schwalb, Heinrich E
Abstract: Splenic artery pseudoaneurysm is a rare phenomenon most associated with chronic pancreatitis or previous trauma. Complications can include erosion and rupture into local structures, a situation that carries a reported mortality of 10–40%. A 58-year-old male with chronic alcoholic pancreatitis and a known splenic artery pseudoaneurysm presented to the emergency department of a regional hospital with rectal bleeding and sepsis. Computed tomography revealed a peri-splenic mass communicating with the splenic flexure. The patient was taken for an emergency splenectomy and left hemicolectomy and was confirmed to have rupture of the splenic artery aneurysm into the large bowel. This case presented with comparable features reported in the literature and demonstrates that access to emergency specialist surgical services in a regional setting offers the capability to manage rare, life threatening surgical emergencies.